CHARACTER OF DISTRIBUTION OF HLA II ANTIGENS IN PATIENTS WITH AVERAGE AND SEVERE FORMS OF ACNE - V. V. Ryabova; S. V. Koshkin; G. A. Zaitseva; A. L. Evseeva (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
This article presents information about the distribution of antigens of the second class in patients with papulo-pustular and nodulous forms of acne. Class II antigens distribution was estimated as the total Group and groups of patients allocated depending on the severity of the clinical picture. Association revealed the presence of severe acne with antigens of histocompatibility of HLA-complex that confirms the importance of immunogenetic factors in the pathogenesis of this condition.